Exploring the trip chaining behaviour of women using public transportation in Ibadan, Nigeria (2013)
Women multi-tasking activities impose a powerful influence on their trip pattern. The study examined the trip sequencing and challenges faced by women using public transport in Ibadan Metropolis. Two hundred and three (203) women were served with structured questionnaire in 10 selected bus stops, using purposive sampling. Only 190 correctly filled questionnaires were subsequently analyzed. Both descriptive and inferential statistics were used for data analysis. Findings indicated that over 40% of women made more than four trips per day. More than 50% of the first trip from home ended in children school. 36.5% and 51.2% of the second and third trips ended up at the place of work respectively. Both fifth and six trips were home bound trips as they accounted for 47.9% and 97.5% respectively. Regression analysis indicated that income and marital status had a significant influence on the number of trips made as both explained 57% of all trips made. Long waiting time at bus stops and misbehavior from conductors and operators were the main challenges faced by women. The paper advocates for improved public transport and enforcement of laws to curb crime and insecurity in public transport.